Art Branding/Art Infusion: Communication of the image and brand identity.: The artist's work as a brand image. - Monteiro, Ilda (2022)
This research work is a literature review study whose theme integrates the concept of brand management in the artistic sphere in order to identify the brand image, with an important contribution to global success. Branding, or brand management, being a strategic and complex challenge, is increasingly used by brands as a tool, to achieve their goals, at a time when competition is evident, whose objective is to produce and prepare a brand to win over customers various types of markets. Theoretically, the question of branding is addressed, with analysis on the repercussions that strategic practices have on the success and evolution of brands. The aim of this work is to analyse the issues related to art branding / art infusion and its associated components in which the image of the work is the artist's brand, whose factors influence the consumer of works of art. Based on this hypothesis, it is essential that professionals in the area consider that there is a relationship between the use of art in advertising communication and the power of influence in the perception of the consuming public. This process is limited to inviting artists already recognized in the community to create artistic pieces of the brand, with emphasis on the advertising object, considering exclusivity, between name recognition, value, branding and notoriety.